Point detection through multi-instance deep heatmap regression for sutures in endoscopy - Sharan, Lalith; Romano, Gabriele; Brand, Julian; Kelm, Halvar; Karck, Matthias; De Simone, Raffaele; Engelhardt, Sandy (International journal of computer assisted radiology and surgery, 2021)
Mitral valve repair is a complex minimally invasive surgery of the heart valve. In this context, suture detection from endoscopic images is a highly relevant task that provides quantitative information to analyse suturing patterns, assess prosthetic configurations and produce augmented reality visualisations. Facial or anatomical landmark detection tasks typically contain a fixed number of landmarks, and use regression or fixed heatmap-based approaches to localize the landmarks. However in endoscopy, there are a varying number of sutures in every image, and the sutures may occur at any location in the annulus, as they are not semantically unique.